2013
DOI: 10.3892/ol.2013.1118
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of B7-H3 increases gemcitabine sensitivity by promoting apoptosis in pancreatic carcinoma

Abstract: In numerous types of cancer, the expression of a novel member of the B7 ligand family, the B7-H3 immunoregulatory protein, has been correlated with a poor prognosis. In the present study, we investigated the role of B7-H3 in chemoresistance in pancreatic carcinoma. Silencing of B7-H3, through lentivirus-mediated delivery of stable short hairpin RNA, was observed to increase the sensitivity of the human pancreatic carcinoma cell line Patu8988 to gemcitabine as a result of enhanced drug-induced apoptosis. Overex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 24 publications
1
47
0
Order By: Relevance
“…Our findings in vivo demonstrated that the B7-H3 silence apparently enhanced the chemosensitivity of rituximab and bendamustine to mantle cell lymphoma in the xenograft model. Similar promoting effects of B7-H3 on cancer resistance to drug treatments in breast cancer (26) and pancreatic carcinoma (27) xenograft models have been reported.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Our findings in vivo demonstrated that the B7-H3 silence apparently enhanced the chemosensitivity of rituximab and bendamustine to mantle cell lymphoma in the xenograft model. Similar promoting effects of B7-H3 on cancer resistance to drug treatments in breast cancer (26) and pancreatic carcinoma (27) xenograft models have been reported.…”
Section: Discussionmentioning
confidence: 51%
“…Liu et al discovered that silencing of B7-H3 sensitized the breast cancer cell lines to paclitaxel by abrogating Jak2/Stat3 phosphorylation (26). In pancreatic carcinoma cells, B7-H3 was demonstrated to induce gemcitabine resistance as well (27). The above research indicated that B7-H3 may be a potential therapeutic target.…”
Section: Introductionmentioning
confidence: 84%
“…Furthermore, it is reported that inhibition of B7-H3 by siRNA significantly suppresses cell migration and invasion, enhances sensitivity to chemotherapeutic drugs in acute monocytic leukemia U937 cells [30]. In pancreatic carcinoma, it is suggested that silencing of B7-H3 increases gemcitabine sensitivity through induction of surviving-dependent apoptosis [31]. In our study, the mRNA and protein levels of B7-H3 were remarkably reduced in NSCLC cells treated with cisplatin and astragaloside IV, suggesting that astragaloside IV increased cisplatin sensitivity via downregulating B7-H3 expression.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have shown that B7-H3 mediates breast cancer invasion, metastasis and drug resistance and that silencing B7-H3 delays tumor growth and sensitizes cancer cells to chemotherapeutic agents (1621). Similar results have also been confirmed by other groups in pancreatic cancer (21,22), colorectal cancer (20), hepatocellular carcinoma (23) and melanoma (19,24). In addition, we and others have shown that B7-H3 overexpression in breast cancer, melanoma and osteosarcoma cells increases their metastatic potential (16,19,25).…”
Section: Introductionmentioning
confidence: 99%